A 360 degree mixed-methods evaluation of a specialized COVID-19 outpatient clinic and remote patient monitoring program - Stacie Vilendrer; Anna Lestoquoy; Maja Artandi; Linda Barman; Kendell Cannon; Donn W. Garvert; Douglas Halket; Laura M. Holdsworth; Sara Singer; Laura Vaughan; Marcy Winget (BMC Primary Care, 2022)
Abstract Background Our goals are to quantify the impact on acute care utilization of a specialized COVID-19 clinic with an integrated remote patient monitoring program in an academic medical center and further examine these data with stakeholder perceptions of clinic effectiveness and acceptability. Methods A retrospective cohort was drawn from enrolled and unenrolled ambulatory patients who tested positive in May through September 2020 matched on age, presence of comorbidities and other factors. Qualitative semi-structured interviews with patients, frontline clinician, and administrators were analyzed in an inductive-deductive approach to identify key themes. Results Enrolled patients were more likely to be hospitalized than unenrolled patients (N = 11/137 in enrolled vs 2/126 unenrolled, p = .02), reflecting a higher admittance rate following emergency department (ED) events among the enrolled vs unenrolled, though this was not a significant difference (46% vs 25%, respectively, p = .32). Thirty-eight qualitative interviews conducted June to October 2020 revealed broad stakeholder belief in the clinic’s support of appropriate care escalation. Contrary to beliefs the clinic reduced inappropriate care utilization, no difference was seen between enrolled and unenrolled patients who presented to the ED and were not admitted (N = 10/137 in enrolled vs 8/126 unenrolled, p = .76). Administrators and providers described the clinic’s integral role in allowing health services to resume in other areas of the health system following an initial lockdown. Conclusions Acute care utilization and multi-stakeholder interviews suggest heightened outpatient observation through a specialized COVID-19 clinic and remote patient monitoring program may have contributed to an increase in appropriate acute care utilization. The clinic’s role securing safe reopening of health services systemwide was endorsed as a primary, if unmeasured, benefit.